Financial Leverage and its Impact on Share Value in Commercial banks "Citigroup Bank as a Model for the Period 2000-2022" (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: The financial leverage, which is called financing by indebtedness or financing by borrowing, which is done by borrowing or issuing indebtedness instruments such as bonds and other financial instruments, is complementary to financing by ownership, which consists of shareholders’ funds and the issuance of shares, so that the financial structure in companies consists of “ownership and indebtedness.”Materials and Methods: The bank's financial leverage was measured through the use of a number of financial ratios, including total liabilities to total assets and total liabilities to total equity, and its impact on the value of the share was measured by using the SPSS program.Conclusions: The results showed that there is a positive correlation between the financial leverage ratios and the value of the share. The value of the share was affected by the mortgage crisis of 2007-2008 AD, as it began to decline in 2007 AD from $359.60 to $29.79 in 2009 AD. From research and study, we find, in addition to the effect of financial leverage, the existence of More than one effect on the stock value.